THU0597 Pulmonary manifestations in mixed connective tissue disease with juvenile and adult onset – are there any differences?. (12th June 2018) - Hetlevik, S.O.; Reiseter, S.; Molberg, Ø.; Flatø, B.; Gunnarsson, R.; Aaløkken, T.M.; Lund, M.B.; Lilleby, V.
Abstract : Background: Mixed connective tissue disease (MCTD) presents in childhood in 7%–23% of cases, but there is limited knowledge about the comparability of juvenile and adult onset of the disease. A common and serious manifestation is interstitial lung disease (ILD), possibly more common in adult MCTD according to a retrospective report[. 1 Objectives: To compare disease variables in juvenile and adult onset MCTD, particularly regarding pulmonary manifestations, after long-term follow-up. Methods: Two cohorts consisting of, respectively, 52 patients with juvenile onset MCTD and 90 patients with adult onset MCTD from all regions of Norway were compared. Inclusion criteria were fulfilment of the Kasukawa- or the Alarcon-Segovia criteria. Patients with onset of symptoms before the age of 18 years were considered to have juvenile onset. All patients were clinically examined, including high resolution CT and pulmonary function tests. Results: Mean age at examination was 28.0 (SD 10.3) in juvenile onset, and 54.3 (SD 13.0) in adult onset MCTD (p<0.001). Age at disease onset was 14.4 (SD4.4) and 37.9 (SD 15.1) years, respectively. Patient and disease characteristics are shown in table 1. Juvenile patients had higher levels of anti-RNP, but lower ESR and CRP compared to adult onset patients. ILD was found in 27% of juvenile and 43% of adult patients (p=0.051), and more adult onset patients had ILD in >20% of total lung volume (TLV). Adult onset patients had lower forced expiratory volume in 1 s (FEV1), but similar diffusing capacity (DLCO) and forced vital capacity (FVC) as the juvenile patients. Conclusions: ILD tended to be more frequent in patients with adult onset MCTD than in those with juvenile onset, although not statistically significant. More patients with adult onset had affection of >20% of TLV. Juvenile and adult patients with similar disease duration had comparable degree of ILD. Juvenile MCTD patients showed higher levels of anti-RNP, but lower ESR and CRP than patients with adult MCTD. Reference: [1] Kotajima L, Aotsuka S, Sumiya M, et al. Clinical features of patients with juvenile onset mixed connective tissue disease: analysis of data collected in a nationwide collaborative study in Japan. J Rheumatol1996;23:1088–94. Disclosure of Interest: None declared